Zagadnienie oznaczania własności mechanicznych fenolowych tworzyw wzmocnionych tkaniną bawełnianą w próbie rozciągania - BROS, Jan (Engineering Transactions, 1966)
The problem of determining, by means of a tensile test, the mechanical properties of phenolics laminated and moulded with chopped cotton fabric filler This paper discusses the conditions of the tensile test that has been performed, also the general investigation method and the procedure for determining the most important mechanical properties of phenolics laminated and moulded with chopped cotton fabric filler. The stress-strain relations, elastic modulus and Poisson’s ratio are described. Later part of the paper contains an analysis of the phenomenon of tension and rupture of a test piece. Some conclusions are drawn.